2019
DOI: 10.32602/jafas.2019.11
|View full text |Cite
|
Sign up to set email alerts
|

Dividend Policy and payout practices in Malaysia: A qualitative analysis

Abstract: Since stock prices reflect the firm's future earnings potentials (Miller and Rock, 1985), dividends announcements therefore convey new information to the market about the future prospects of the corporation. As such, the objective of the current study is t potential role that dividend payouts play in influencing the fund managers and investors in recommending or selecting a stock, and for various stocks' performance assessment. In addition, the study attempts to examine the possible effect of taxation on divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…The maximization of shareholder wealth is one of the most important objectives of companies by maximizing their value. Consequently, there are many decisions that can affect the company's value, such as financing decisions that determine whether they should rely on external financing such as debt, By using retained earnings instead of borrowing, and thus the trade-off between the distribution of profits or the holding of owners in order to reinvest them for expansion and growth (Said Omar & Echchabi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The maximization of shareholder wealth is one of the most important objectives of companies by maximizing their value. Consequently, there are many decisions that can affect the company's value, such as financing decisions that determine whether they should rely on external financing such as debt, By using retained earnings instead of borrowing, and thus the trade-off between the distribution of profits or the holding of owners in order to reinvest them for expansion and growth (Said Omar & Echchabi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Researcher found that the market reacts to the announcement of dividend which is indicated by the existence of abnormal return value which is directly proportion to increase and decrease in dividends which strengths the perspective of signalling theory. The work of Omar and Echchabi (2019) examined the potential role of dividend pay-out plays in influencing the fund managers in selecting and recommending a stock. Semi-structured interview method was conducted with six Malaysian investment manager and the results indicates that other factors coupled with dividend pay-out pays a catalyst for investors and fund managers to select a stock in their portfolio.…”
Section: Effect Of Dividend Policy and Dpo On Firm Performancementioning
confidence: 99%
“…Berdasarkan residual theory of dividend, pendanaan terhadap peluang investasi yang menguntungkan harus dilakukan terlebih dahulu sebelum dividen dibayarkan (Brigham & Gapenski, 1996dalam Usman, 2006 dan pembayaran dividen dilakukan apabila masih terdapat arus kas sisa (Omar & Echchabi, 2019). Hal tersebut dikarena perusahaan cenderung membiayai proyek investasi menggunakan dana internal (Bhagwat & Debruine, 2009dalam Yeo, 2018 daripada menggunakan dana eksternal karena lebih murah (Wulandari & Suardana, 2017), sehingga manajemen akan memilih menahan laba untuk investasi dibandingkan membagikan dividen dalam jumlah yang tinggi.…”
Section: Pendahuluanunclassified